Third-order operator-differential equations with discontinuous coefficients and operators in the boundary conditions - Araz R. Aliev; Nazila L. Muradova (Electronic Journal of Differential Equations, 2013)
We study a third-order operator-differential equation on the semi-axis with a discontinuous coefficient and boundary conditions which include an abstract linear operator. Sufficient conditions for the well-posed and unique solvability are found by means of properties of the operator coefficients in a Sobolev-type space.